An Early Bronze Age burial with a golden spiral ring from Ammerbuch-Reusten, southwestern Germany - Krauß, Raiko; Breuer, Lea; Korolnik, Simone; Pernicka, Ernst; Schorer, Birgit; Spatzier, André; Stein, Veronika; Bofinger, Jörg (Prähistorische Zeitschrift, 2021)
Zusammenfassung des Textes in deutscher Sprache
Keywords: Ammerbuch-Reusten